The Halab deposit, SW Zanjan: Volcanogenic massive sulfide Zn–Pb (Ag) mineralization, Takab–Takht-e-Soleyman–Angouran metallogenic district - Fatemeh Karami; Hossein Kouhestani; Mir Ali Asghar Mokhtari; Amir Morteza Azimzadeh (Journal of Economic Geology, 2021)
Introduction The Halab Zn–Pb (Ag) deposit, 125-km southwest of Zanjan, is located in the Takab–Takht-e-Soleyman–Angouran metallogenic district (TTAMD), Sanandaj-Sirjan zone. Several types of deposits are present in the TTAMD, including nonsulfide Zn–Pb deposits, sediment-hosted epithermal gold deposits, epithermal precious and base metal deposits, skarn and volcano-sedimentary iron deposits, and massive sulfide Pb-Zn (Ag) deposits. The most important deposits discovered to date within the TTAMD are the Angouran nonsulfide Zn–Pb deposit (Gilg et al., 2006; Boni et al., 2007; Daliran et al., 2013), Zarshuran sediment-hosted epithermal gold deposit (Mehrabi et al., 1999; Asadi et al., 2000; Daliran et al., 2002), and Agdar’reh epithermal gold deposit (Daliran, 2008). Other important deposits or occurrences include Touzlar, Ay Qalasi, Arabshah, Qozlou, Shahrak, Goorgoor, Mianaj, and Halab (Heidari et al., 2015; Mohammadi Niaei et al., 2015; Najafzadeh et al., 2017; Nafisi et al., 2019). To date, no detailed study has been reported to understand the characteristics of Zn–Pb (Ag) mineralization at the Halab deposit. This paper presents the geologic framework, mineralization characteristics, and lithogeochemical signatures of the Halab deposit with emphasis on ore genesis. Identification of these characteristics can serve as a model for exploration of Zn–Pb (Ag) mineralization in the Halab area and other parts of the TTAMD.